Electromagnetic Magnetoplasmic Wave in Multi-layer Resonator With Several - Gaivenis, R.; Laurinavičius, L.; Jankauskas, Z. (Elektronika ir Elektrotechnika, 2004)
The electromagnetic magnetoplasmic wave resonance in multi-layer semiconductor structure are investigated. For several semiconductors resonator makes calculation method, program for PC, analyze of calculations results are described. The influence of the air clearance between the semiconductor layers is considered. Especially we have sharp resonant peaks in the case when the thickness of air clearance and semiconductor layers is of the same order. For the materials with higher carrier mobility the resonant curves are much narrower and higher. The strong dependence of the main resonance from the magnetic field is observed. Ill. 14, bibl. 3 (in Lithuanian; summaries in Lithuanian, English, Russian).